2022
DOI: 10.3390/ani12212972
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Rapeseed Meal in Diets for Piglets on Blood Biochemical Parameters and the Microbial Composition of the Feed and Faeces

Abstract: The study assessed the influence of rapeseed meal (RSM) fermented using Bacillus subtilis 87Y on the feed microbiota, intestinal microbiota, blood biochemical parameters, and content of minerals in the blood plasma and faeces of piglets. Modulation of the microbial composition of feed containing fermented rapeseed meal (FRSM) and of the faeces of pigs consuming it was observed. There was a significant increase in the number of lactic acid bacteria (LAB) and a decrease in the total number of coliforms and Clost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The ALP not only benefits the formation of hard tissue, especially bones, but also has anti-inflammatory functions ( 44 ). We found that the wheat bran fermented by B. licheniformis significantly increased serum ALP activity of pigs, which was consistent with previous studies in piglets ( 45 ) and tilapia fish ( 46 ). This might be due to the presences of abundant enzyme activities (phytase and enzymes that hydrolyze non starch polysaccharide components) in fermented feed, leading to an increase in mineral intake during the ossification process ( 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…The ALP not only benefits the formation of hard tissue, especially bones, but also has anti-inflammatory functions ( 44 ). We found that the wheat bran fermented by B. licheniformis significantly increased serum ALP activity of pigs, which was consistent with previous studies in piglets ( 45 ) and tilapia fish ( 46 ). This might be due to the presences of abundant enzyme activities (phytase and enzymes that hydrolyze non starch polysaccharide components) in fermented feed, leading to an increase in mineral intake during the ossification process ( 47 ).…”
Section: Discussionsupporting
confidence: 92%
“…It is important to note that research has shown that feeding fermented soybean meal to growing pigs (17.46 ± 1.97 kg) instead of regular soybean meal greatly decreased the amount of Escherichia coli in the colon while dramatically increasing the amount of Lactobacillus ( 51 ). In a similar vein, it was also found that the addition of fermented soybean meal instead of soybean meal could significantly increase the number of lactic acid bacteria in the feces of piglets (7 kg), while concurrently reducing the total count of Coliforms and Clostridium perfringens ( 52 ). This outcome is attributable to the fermentation of rapeseed meal.…”
Section: Discussionmentioning
confidence: 78%
“…Analyzing the biochemical parameters of the piglets involved in the study revealed several key observations. Firstly, AST activity in the FR-15 and FR-25 groups, along with uric acid levels in all groups, and cholesterol and triglyceride contents -particularly in the NC group -were observed to be higher than reference values for adult pigs (Winnicka, 2021). These anomalies are believed to stem from an excessive intake of easily digestible protein in the piglets' diet.…”
Section: Discussionmentioning
confidence: 88%
“…Post-extraction rapeseed meal, a by-product of rapeseed oil extraction, is a valuable source of raw protein (30-42%) and is widely used in the feeding of farm animals due to its market availability (Gołębiowska et al, 2022). However, the presence of anti-nutritional factors (ANFs), such as glucosinolates, tannins, non-starch polysaccharides, and phytic compounds, significantly limits its use, particularly in monogastric animals (Wlazło et al, 2022;Winiarska-Mieczan et al, 2023). This issue is especially problematic for gestating sows (Czech et al, 2022), which are prone to metabolic syndrome and oxidative stress (Li et al, 2021) and for piglets, whose digestive tracts are sensitive to antinutritional substances (Zhu et al, 2017;Czech et al, 2021 a, b).…”
mentioning
confidence: 99%